KONSUMSI AIR PUTIH, STATUS GIZI, DAN STATUS KESEHATAN PENGHUNI PANTI WERDA DI KABUPATEN PACITAN - Aprillia, Desy Dwi; Khomsan, Ali (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to learn and analyze the relationship between the consumption of plain water, nutritional status, and health status of panti werda residents in Pacitan. Design of this study was cross-sectional. Subject of this study were panti werda residents. As many as 24 people were chosen as subject. This result showed that 75% of subject had plain water sufficient levels were categorized as adequate and 25% were inadequate. Energy and protein sufficiency levels of subject were 33% and 42% categorized as normal. Micronutrient sufficient levels of subject consists of 83% phosphorus, 88% iron, and 100% vitamin A were categorized as adequate, but calcium and vitamin C sufficient levels as many as 96% and 100% were categorized as inadequate. As many as 42% subject had normal nutritional status, 25% were underweight, and 33% were overweight. Health status of subject as many as 54% were categorized as high and 46% were low. The Pearson and Spearman correlation test showed that nutritional status with nutrient intake, plain water consumption, and health status of subject had no significant relationship (p>0.05).